Chemical Stability of Metal Halide Perovskite Detectors - Bin Zhang; Bin Xue; Shuang Xiao; Xingzhu Wang (Inorganics, 2024)
Metal halide perovskite (MHP) detectors are highly esteemed for their outstanding photoelectric properties and versatility in applications. However, they are unfortunately prone to degradation, which constitutes a significant barrier to their sustained performance. This review meticulously delves into the causes leading to their instability, predominantly attributable to factors such as humidity, temperature, and electric fields and, notably, to various radiation factors such as X-rays, γ-rays, electron beams, and proton beams. Furthermore, it outlines recent advancements in strategies aimed at mitigating these detrimental effects, emphasizing breakthroughs in composition engineering, heterostructure construction, and encapsulation methodologies. At last, this review underscores the needs for future improvements in theoretical studies, material design, and standard testing protocols. In the pursuit of optimizing the chemical stability of MHP detectors, collaborative efforts are in an imperative need. In this way, broad industrial applications of MHP detectors could be achieved.